2015
DOI: 10.3389/fnagi.2015.00030
|View full text |Cite
|
Sign up to set email alerts
|

Regional and sub-regional differences in hippocampal GABAergic neuronal vulnerability in the TgCRND8 mouse model of Alzheimer's disease

Abstract: Hippocampal network activity is predominantly coordinated by γ-amino-butyric acid (GABA)ergic neurons. We have previously hypothesized that the altered excitability of hippocampal neurons in Alzheimer's disease (AD), which manifests as increased in vivo susceptibility to seizures in the TgCRND8 mouse model of AD, may be related to disruption of hippocampal GABAergic neurons. In agreement, our previous study in TgCRND8 mice has shown that hippocampal GABAergic neurons are more vulnerable to AD-related neuropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 33 publications
10
56
2
Order By: Relevance
“…Immunohistochemical staining for three neuronal markers (NeuN, NPY and PV) revealed distributional patterns in CA1/2, CA3, DG and subiculum (Figure 1A) that have been described previously (Albuquerque et al, 2015). Assessment of Aβ and amyloid-plaques using the FCA3340 antibody, which specifically recognizes human Aβ but not APP (Barelli et al, 1997), indicated no immunolabeling in hippocampus sections obtained from 1 month-old TgCRND8 mice, in contrast to the abundance of plaques present in the hippocampus of 11 month-old TgCRND8 mice, used as a positive control (Chishti et al, 2001; Figure 1B).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Immunohistochemical staining for three neuronal markers (NeuN, NPY and PV) revealed distributional patterns in CA1/2, CA3, DG and subiculum (Figure 1A) that have been described previously (Albuquerque et al, 2015). Assessment of Aβ and amyloid-plaques using the FCA3340 antibody, which specifically recognizes human Aβ but not APP (Barelli et al, 1997), indicated no immunolabeling in hippocampus sections obtained from 1 month-old TgCRND8 mice, in contrast to the abundance of plaques present in the hippocampus of 11 month-old TgCRND8 mice, used as a positive control (Chishti et al, 2001; Figure 1B).…”
Section: Resultssupporting
confidence: 80%
“…As with the aforementioned CA1 synaptic hyperexcitability, our results indicate that the change in the composition of certain GABAergic sub-populations may occur much earlier than previously believed. This is particularly striking for NPY-expressing GABAergic neurons that, by the age of 1 month (in the present study), have already decreased substantially in number, similar to 6 month-old TgCRND8 mice (Albuquerque et al, 2015) in all studied hippocampal regions. By contrast, the alteration of PV-expressing neurons appears more complex because the decreased expression of PV found in CA1 and subiculum at 1 month of age is not detectable in 6 month-old animals (Albuquerque et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In AD, there is a clear loss of SOM innervation (reviewed in (Martel, et al, 2012) and several studies with APP transgenic mice support that SOM+ cells may be highly vulnerable to pathological Aβ accumulation (Albuquerque, et al, 2015,Ma and McLaurin, 2014,Perez-Cruz, et al, 2011,Ramos, et al, 2006). The sensitivity of these specific interneurons to AD pathology may relate to their putatively high capacity for intracellular Aβ metabolism via expression of ECE-2.…”
Section: Discussionmentioning
confidence: 99%